2014
DOI: 10.3109/02699052.2014.891761
|View full text |Cite
|
Sign up to set email alerts
|

Blast-related mild traumatic brain injury in the acute phase: Acute stress reactions partially mediate the relationship between loss of consciousness and symptoms

Abstract: Results suggest ASR may partially mediate symptom presentation and cognitive dysfunction in the acute phase following blast-related mTBI. Future research is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 57 publications
0
24
0
Order By: Relevance
“…Norris showed that TBI with loss of consciousness (LOC) was associated with greater self-reported difficulty sleeping compared to TBI without LOC in 210 active duty SMs who reported sustaining an mTBI to a US military-operated concussion clinic in Afghanistan. The greatest self-reported sleep difficulty associated with LOC was endorsed at 72 hours post-injury and again 48-72 hours after the initial TBI assessment (Norris, Sams, Lundblad, Frantz, & Harris, 2014). These findings suggest that the onset of sleep disturbance can occur immediately following the point of injury and are strongly associated with LOC.…”
Section: Time Course Of Sleep Disturbances and Tbimentioning
confidence: 71%
“…Norris showed that TBI with loss of consciousness (LOC) was associated with greater self-reported difficulty sleeping compared to TBI without LOC in 210 active duty SMs who reported sustaining an mTBI to a US military-operated concussion clinic in Afghanistan. The greatest self-reported sleep difficulty associated with LOC was endorsed at 72 hours post-injury and again 48-72 hours after the initial TBI assessment (Norris, Sams, Lundblad, Frantz, & Harris, 2014). These findings suggest that the onset of sleep disturbance can occur immediately following the point of injury and are strongly associated with LOC.…”
Section: Time Course Of Sleep Disturbances and Tbimentioning
confidence: 71%
“…Numerous studies have shown an association between blast-related (and non-blast-related) TBI and deficits in physiological and cognitive abilities (Norris et al, 2014;Scheibel et al, 2012). See Bogdanova and Verfaellie (2012) for review.…”
Section: Blast Exposurementioning
confidence: 99%
“…This question has been tested recently with mixed results. According to several studies, differences do not exist between blast and non-blast-related TBI on measures of postconcussion symptom endorsement and various neuropsychological and cognitive measures (Cooper et al, 2012;Luethcke et al, 2011;Neipert et al, 2014;Norris et al, 2014). Differences between blast and non-blast-related TBI have been demonstrated, however, on measures of white matter integrity (Taber et al, 2014) and neural activation during response inhibition (Fischer et al, 2014) using magnetic resonance imaging.…”
Section: Blast Exposurementioning
confidence: 99%
“…Unfortunately, multiple decision criteria (New Orleans Criteria, Canadian CT Head Rule) identifying which patients are at risk of having an ICH after TBI have excluded patients without documented LOC (24,25). This exclusion criterion removes 30 to 50% of all TBI patients, a large proportion of which might be at risk of having a symptom-free ICH due to age-related cerebral atrophy (4)(5)(6)(7)(8)(9). There is a need for more research investigating if the risk of an in-hospital delayed ICH is modified by the presence or absence of documented LOC following a mTBI.…”
Section: Discussionmentioning
confidence: 99%
“…Across nearly 2,500 patients with a Glasgow coma scale (GCS) of 15, the risk of documented LOC was 69% (4). Similarly, in a population of 210 blastrelated TBIs, the risk of documented LOC was 68% (5). In other studies examining mild to moderate TBI, however, the risk of documented LOC was lower (40-55%) (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%